Phase equilibria of the Al-Co-Er system at 400°C and 600°C - Zheng L.-H.; Zhang L.-G.; Zhao F.-Y.; Liu L.-B.; Wang D.; Wu C.-J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The 400°C and 600°C isothermal sections of the Al–Co–Er system were studied assisted with X-ray diffraction (XRD), scanning electron microscopy (SEM), and electron probe microanalysis (EPMA) techniques. 18 three-phase fields were identified in the 400°C isothermal section. The maximum solid solubilities of Al in Co3Er and Co2Er were 13.93 at.%, and 16.13 at.%, respectively whereas the maximum solid solubilities of Co in Al2Er, Al2Er3 and AlEr2 were 6.93 at.%, 6.65 at.%, and 6.49 at.%, respectively. The solid solution range of λ is from 22.22 at.% Al to 44.44 at.% Al while the 600°C isothermal section included 20 three-phase fields. The maximum solid solubilities of Al in Co17Er2 and Co7Er2 were 10.17 at.% and 10.24 at.%, respectively. The maximum solid solubilities of Co in Al2Er and Al2Er3 were 3.63 at.% and 2.01 at.%, respectively.